First description and diagnostics of disease caused by Piscirickettsia salmonis in farmed European sea bass ( Dicentrarchus labrax Linnaeus) from Croatia - Snježana Zrnčić; Niccolò Vendramin; Torsten S. Boutrup; Mette Boye; Lone Madsen; Bettina Nonneman; Dragan Brnić; Dražen Oraić (Journal of Fish Diseases, 2021)
During the winter of 2013 and 2016, several Croatian fish farms experienced mortalities in the fry of European sea bass, Dicentrarchus labrax . Affected fish showed abnormal swimming behaviour and reduced appetite, and death ensued several days after the onset of clinical signs of disease. Necropsy revealed pale liver, empty digestive tract, distended gall bladder, and hyperaemia and congestion of the meninges. Routine bacteriological examination tested negative, and virological examination ruled out nodavirus infection. Histological examination revealed multifocal necrosis and extensive inflammation in the brain with abundant cellular debris in the ventricles. Inflammatory cells displayed intra‐cytoplasmic basophilic vacuoles leading to suspicion of Piscirickettsia salmonis infection. Fluorescent in situ hybridization using an oligonucleotide probe targeting Domain Bacterium applied to tissue sections tested positive. The pathogen was identified by 16S rRNA gene sequencing of brain material, and the sequence showed 99% similarity with P. salmonis . This result enabled the design of an oligonucleotide probe specifically targeting P. salmonis . In 2016, P. salmonis was successfully isolated on CHAB from the brain of an affected specimen and identified using 16S rRNA gene sequencing and MALDI‐TOF. This study describes the first outbreak of disease caused by P. salmonis in sea bass in Croatia, while new diagnostic tools will enable further research on its epidemiology and pathogenicity.